(untitled) (Czech Journal of Multidisciplinary Innovations, 2023)
The article is devoted to determining the possibilities of professional self-development of future teachers in the system of traditional and competence-activity approaches in higher education institutions. The essence of professional self-development and the conditions of the educational environment aimed at ensuring it are based. A comparative analysis of these approaches was carried out, their specific features were determined.